Peripheral Nerve Injuries of The Upper Extremity - Result of Late Repair - Dr. Siti Roy Chowdhury; Dr. A. Mukherjee (Indian Journal of Plastic Surgery)
One hundred different types of peripheral nerve injuries of the upper extremity in eighty patients is the subject of study. The results of late repair between 3 months and 1 year and functional recovery thereof has been studied, both clinically and electrophysiologically. Better results are observed in children and teenagers as compared to adults. Clinical evidence of recovery is a better guide than the electrophysiological findings.